Utilization of surgical safety checklists by urological surgeons in Germany: a nationwide prospective survey. Issue 1 (December 2015) - Borgmann, Hendrik; Helbig, Sarah; Reiter, Michael; Hüsch, Tanja; Schilling, David; Tsaur, Igor; Haferkamp, Axel
Abstract Objectives We aimed to investigate the contemporary usage rate and habits of the WHO Surgical Safety Checklist (SSC) in German urological departments. Methods We designed a 26-item questionnaire that was sent to all urological departments in Germany. The primary aim of this study was to evaluate the usage rate of the SSC. Secondary aims were to compare perioperative characteristics of users vs. non-users of the SSC and to assess circumstances of the SSC application. Results A total of 213 of 234 (91 %) urological departments were users of the SSC, and 21 (9 %) were non-users. SSC users had more often a standard protocol, took less time and had fewer people involved for checking perioperative patient data compared to non-users. Financial budgeting for the SSC existed in 55 (24 %) departments and for patient safety in 73 (32 %) departments. Conclusions The usage rate of the SSC in urological departments in Germany is high despite restricted financial budgeting. Users of the SSC profit by saving time and manpower for checking perioperative patient data.